Effects of arginine vasopressin on musical working memory - Granot, Roni Y.; Uzefovsky, Florina; Bogopolsky, Helena; Ebstein, Richard P. (Frontiers in Psychology, 2013)
Previous genetic studies showed an association between variations in the gene coding for the 1a receptor of the neuro-hormone arginine vasopressin (AVP) and musical working memory (WM). The current study set out to test the influence of intranasal administration (INA) of AVP on musical as compared to verbal WM using a double blind crossover (AVP – placebo) design. Two groups of 25 males were exposed to 20 IU of AVP in one session, and 20 IU of saline water (placebo) in a second session, one week apart. In each session subjects completed the tonal subtest from Gordon's Musical Aptitude Profile, the interval subtest from the Montreal Battery for Evaluation of Amusias (MBEA), and the forward and backward digit span tests. Scores in the digit span tests were not influenced by AVP. In contrast, in the music tests there was an AVP effect. In the MBEA test, scores for the group receiving placebo in the first session (PV) were higher than for the group receiving vasopressin in the first session (VP) (p < .05) with no main Session effect nor Group * Session interaction. In the Gordon test there was a main Session effect (p < .05) with scores higher in the second as compared to the first session, a marginal main Group effect (p = .093) and a marginal Group X Session interaction (p = 0.88). In addition we found that the group that received AVP in the first session scored higher on scales indicative of happiness, and alertness on the Positive and Negative Affect Scale, (PANAS). Only in this group and only in the music test these scores were significantly correlated with memory scores. Together the results reflect a complex interaction between AVP, musical memory, arousal, and contextual effects such as session, and base levels of memory. The results are interpreted in light of music's universal use as a means to modulate arousal on the one hand, and AVP's influence on mood, arousal, and social interactions on the other.